The duty to disclose adverse clinical trial results. - Liao, S; Sheehan, M; Clarke, S (2009)
Participants in some clinical trials are at risk of being harmed and sometimes are seriously harmed as a result of not being provided with available, relevant risk information. We argue that this situation is unacceptable and that there is a moral duty to disclose all adverse clinical trial results to participants in clinical trials. This duty is grounded in the human right not to be placed at risk of harm without informed consent. We consider objections to disclosure grounded in considerations of commercial interest, and we argue that these concerns are insufficient to override the moral duty to disclose adverse clinical trial results. However, we also develop a proposal that enables commercial interests to be protected, while promoting the duty to disclose adverse clinical trial results.